THE APPLICATION OF POLLEN RADIOCARBON DATING AND BAYESIAN AGE-DEPTH MODELING FOR DEVELOPING ROBUST GEOCHRONOLOGICAL FRAMEWORKS OF WETLAND ARCHIVES. Issue 2 (27th April 2022) - Cadd, Haidee; Sherborne-Higgins, Bryce; Becerra-Valdivia, Lorena; Tibby, John; Barr, Cameron; Forbes, Matt; Cohen, Tim J; Tyler, Jonathan; Vandergoes, Marcus; Francke, Alexander; Lewis, Richard; Arnold, Lee J; et al.
ABSTRACT: Wetland sediments are valuable archives of environmental change but can be challenging to date. Terrestrial macrofossils are often sparse, resulting in radiocarbon ( 14 C) dating of less desirable organic fractions. An alternative approach for capturing changes in atmospheric 14 C is the use of terrestrial microfossils. We 14 C date pollen microfossils from two Australian wetland sediment sequences and compare these to ages from other sediment fractions (n = 56). For the Holocene Lake Werri Berri record, pollen 14 C ages are consistent with 14 C ages on bulk sediment and humic acids (n = 14), whilst Stable Polycyclic Aromatic Carbon (SPAC) 14 C ages (n = 4) are significantly younger. For Welsby Lagoon, pollen concentrate 14 C ages (n = 21) provide a stratigraphically coherent sequence back to 50 ka BP. 14 C ages from humic acid and >100 µm fractions (n = 13) are inconsistent, and often substantially younger than pollen ages. Our comparison of Bayesian age-depth models, developed in Oxcal, Bacon and Undatable, highlight the strengths and weaknesses of the different programs for straightforward and more complex chrono-stratigraphic records. All models display broad similarities but differences in modeled age-uncertainty, particularly when age constraints are sparse. Intensive dating of wetland sequences improves the identification of outliers and generation of robust age models, regardless of program used.